EFFECT OF PLANT EXTRACTS ON SPORULATION AND SPORE GERMINATION OF STORED MELON SEED FUNGI - E., Amadi; E., deleke; G., Olahan; T., Garuba; M.O., Adebola (International Journal of Research -GRANTHAALAYAH, 2014)
Frequently, stored melon seeds fail to preserve to their time of use. Storage fungi invade these seeds and cause their deterioration. A study was, therefore, carried out to determine the effect of guava (Psidiumguajava L.) leaf and ginger (Zingiberofficinale) rhizome extracts on the sporulation and spore germination of the invading seed fungi.Dried leaves and rhizomes were ground in sterile mortar, filtered through a wire sieve and then extracted usingthree different solvents. Results revealed that both extracts hindered sporulation and spore germination in the four fungi tested namely: Aspergillusflavus, A. niger, Rhizopusstolonifer and Fusarium species. The effect of the extracts on the test organisms increased with concentration of the extracts. Phytochemical screening confirmed the presence of alkaloids, saponins, lipids,tannins, flavonoids, and steroids. A reduction in nutrient contents was also observed in infested melon seeds. These results are significant and would serve as a template for planning the control of storage fungi in melon seeds in particular and other crop produce in general.